2007
DOI: 10.1017/s0967199406003947
|View full text |Cite
|
Sign up to set email alerts
|

Somatic cell nuclear transfer using transported in vitro-matured oocytes in cynomolgus monkey

Abstract: Somatic cell nuclear transfer (SCNT) is not successful so far in non-human primates. The objective of this study was to investigate the effects of stimulation cycles (first and repeat) on oocyte retrieval and in vitro maturation (IVM) and to evaluate the effects of stimulation cycles and donor cell type (cumulus and fetal skin fibroblasts) on efficiency of SCNT with transported IVM oocytes. In this study, 369 immature oocytes were collected laparoscopically at 24 h following human chorionic gonadotrophin (hCG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…As some research studies have shown that PLM does not have detrimental effects on oocyte developmental competence, researchers have been using PLM to enucleate oocytes from mice and hamsters (Liu et al 2000a), cattle (Lu et al 2005) and non-human primates (Chen et al 2007;Mitalipov et al 2007) with promising results. In addition, rhesus macaque embryos were produced for nuclear transfer of adult skin fibroblasts with the aid of PLM to enucleate the oocytes.…”
Section: Enucleation By Plm -Nuclear Transfermentioning
confidence: 99%
“…As some research studies have shown that PLM does not have detrimental effects on oocyte developmental competence, researchers have been using PLM to enucleate oocytes from mice and hamsters (Liu et al 2000a), cattle (Lu et al 2005) and non-human primates (Chen et al 2007;Mitalipov et al 2007) with promising results. In addition, rhesus macaque embryos were produced for nuclear transfer of adult skin fibroblasts with the aid of PLM to enucleate the oocytes.…”
Section: Enucleation By Plm -Nuclear Transfermentioning
confidence: 99%
“…This approach results in an enucleation rate that varies widely among laboratories (40%-90%) depending on the skill and experience of the operators; it is usually difficult to reach a high enucleation rate due to "blind" localization of the nucleus [2][3][4][5] . To increase enucleation efficiency, spindle imaging system-assisted (SIS-A) enucleation has been used for oocyte enucleation in pig, cattle and other species [6][7][8][9][10][11][12][13] . This method employs a polarized light microscope to visualize the meiotic spindle-containing oocyte nucleus.…”
Section: Introductionmentioning
confidence: 99%
“…This method employs a polarized light microscope to visualize the meiotic spindle-containing oocyte nucleus. The SIS-A approach can achieve a high oocyte enucleation rate (88%-100%) in several mammalian species [8,10,12,13] and improve the in vitro development efficiency of cloned embryos in pigs and cattle [6,7] . Fluorescence dye staining has also been used to localize clearly the oocyte nucleus before enucleation [14,15] .…”
Section: Introductionmentioning
confidence: 99%